2018
DOI: 10.1093/geront/gny017
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in People With Severe Dementia and Its Association With the Environment in Nursing Homes: An Observational Study

Abstract: Structural and organizational characteristics of care units, which in turn have implications for residents characteristics and the quality of care, may influence the QoL of residents. This may explain the interaction we observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In fact, the results of our subsequent analysis con rmed these assumptions only partly. Finally, we could not show that residents of dementia-speci c (segregated) living units or small living units had better care outcomes compared to residents from other living units [20]. One reason why we did not nd the expected results may be the a priori de nition of the living unit types.…”
Section: Introductionmentioning
confidence: 64%
“…In fact, the results of our subsequent analysis con rmed these assumptions only partly. Finally, we could not show that residents of dementia-speci c (segregated) living units or small living units had better care outcomes compared to residents from other living units [20]. One reason why we did not nd the expected results may be the a priori de nition of the living unit types.…”
Section: Introductionmentioning
confidence: 64%
“…In order to test the main hypothesis, a sum score was created across all 37 items at baseline. Further, we studied the determinants of QoL according to the literature [25][26][27] to establish nine subscales: care relationship (7 items), positive affect (6 items), negative affect (3 items), restlessness (3 items), positive self-image (3 items), social relationship (6 items), social isolation (3 items), feeling at home (4 items), and having something to do (2 items) (Table). These subscales are sum scores across the respective items, which were presented in a Likert format ranging from never (0), rarely (1), and sometimes (2) to frequently (3).…”
Section: Methodsmentioning
confidence: 99%
“…The varimax-rotated PCA solution accounted for 67.2% of the overall variance. Next to the subscales, we created a composite sum score across all 37 items, which has been used extensively in the literature as well [25][26][27][28][29][30]. Thus, in our analyses, we look into both the comprehensive sum score (Table 2) as well as subscale results ( 'positive affect', 'negative affect', 'restlessness', and 'social relationships' of the full 37-item version of QUALIDEM (i.e., subscale B, subscale C, subscale D, and subscale F) [8,31].…”
Section: Methodsmentioning
confidence: 99%
“…Current research proposes the implementation of quality of life measurements to cover residents' viewpoints on care (Becker et al 2005;Brandenburg & Günther 2015;de Boer et al 2017;Grabowski et al 2014;Hassler & Wolf-Ostermann 2010;Kok et al 2018;Palm et al 2018;Vaarama et al 2008). So far only a few studies investigating subjective quality of life in older people can be found.…”
Section: Introductionmentioning
confidence: 99%
“…So far only a few studies investigating subjective quality of life in older people can be found. They mainly focus on older, multi-morbid patients without dementia (Hassler & Wolf-Ostermann 2010;Holzhausen 2009;Warnke et al 2004), address patients with dementia partly in special settings (Auer, et al 2017;Ettema et al 2005;Gertz & Berwig 2008;Kok et al 2018;Logsdon et al 2002;Palm et al 2018;Sixsmith et al 2008), and consider care-related measures in nursing home residents (Becker et al 2005;Schaal et al 2015;Vaarama et al 2008). According to our research there is still a complete lack of studies on groupliving nursing homes residents in Germany and elsewhere, apart from one preliminary pilot study published in 2013.…”
Section: Introductionmentioning
confidence: 99%